Zanthoxylum armatum DC.: Current knowledge, gaps and opportunities in Nepal. (30th January 2019) - Phuyal, Nirmala; Jha, Pramod Kumar; Prasad Raturi, Pankaj; Rajbhandary, Sangeeta
Abstract: Ethnopharmacological relevance: Zanthoxylum armatum DC. possesses several medicinal properties and has been commonly used in different indigenous medicinal practices to cure several diseases because of its stomachic, carminative and anthelmintic properties. Aim: This review paper aims to provide an update on and analysis of information about the ecology, uses, phytochemistry, pharmacology, trade opportunities, policy gaps for the commercialization of this species forming a basis for further scientific innovations Materials and methods: Information was gathered through a search of different books, journals, articles, annual reports, proceedings and web-based materials. Result: Alkaloids, sterols, phenolics, lignins coumarins, terpenoids and flavonoids have been identified from leaves, fruits, stem, bark and seeds. Its trade value is also very high with its manifold applications in Ayurveda, allopathy, general pharmacy, and other industries. Antimicrobial, antiviral, antioxidant, anti-inflammatory, cytotoxic, hepato-protective, insecticidal/larvicidal effects are of particular relevance. Conclusion: It is one of the prioritized medicinal plants for economic development in Nepal. Owing to its diverse applications, the species can be developed as an important commodity for alleviation of poverty in rural areas. The various ethno-pharmacological applications of Zanthoxylum armatum have been verified by several related researches. More extensive study on the individual specific phyto-component can lead to novel innovations for the well-being of mankind. Graphical abstract: